Kaninong Buhay ang Uunahin Ko?: The Lived Experiences of Anakina Providing Dual Caregiving for Their Children and Mothers with Dementia - Embudo, Angel; Lontoco, Deinne Ann; Buesing, Alden Andrei (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explores the lived experiences of Filipina middle-aged solo parents (Anakina) who simultaneously provide care for their dependent children and mothers with dementia within the collectivistic Filipino context. Anchored in the Sandwich Generation concept and the Acceptance Theory of Family Caregiving, the research employs a qualitative hermeneutic phenomenological design to examine the challenges, coping mechanisms, perceived benefits, and culturally grounded caregiving practices of participants. Data were collected through semi-structured face-to-face interviews with three purposively selected participants from Cavite, Laguna, and Manila, and analyzed using Interpretative Phenomenological Analysis (IPA). Findings reveal that Anakina face significant challenges, including solo caregiving responsibility, physical exhaustion, and emotional strain intensified by financial pressures and limited support systems. Despite these burdens, participants demonstrated resilience through adaptive coping strategies such as seeking social support, engaging with digital resources, and practicing positive reframing, although maladaptive responses occurred during periods of extreme stress. The study also highlights positive outcomes, including strengthened relationships with children, shared caregiving responsibilities, and increased emotional acceptance and personal growth. Filipino cultural values, particularly utang na loob and spiritual faith, emerged as central influences that both sustain caregiving commitment and contribute to caregiver burden. The study concludes that while dual caregiving presents substantial physical and emotional challenges, culturally rooted values and adaptive coping mechanisms enable caregivers to sustain their roles. It recommends enhanced access to culturally sensitive mental health services, strengthened family and community support systems, and government interventions to alleviate caregiver burden. The study aligns with SDG 3 (Good Health and Well-Being), SDG 5 (Gender Equality), SDG 8 (Decent Work and Economic Growth), and SDG 10 (Reduced Inequalities), as it addresses caregiver health, gendered caregiving roles, economic strain, and disparities in support systems. Its sustainability impact lies in informing policies and community-based interventions that support caregiver welfare, promote inclusive health systems, and strengthen culturally responsive caregiving frameworks.
Keywords: Acceptance Theory of Family Caregiving; Dementia Caregiving; Filipina Solo Parents; Hermeneutic Phenomenology; Sandwich Generation; Social Support; Spiritual Faith; Utang Na Loob